Studi Eksperimental Pembuatan Biogas dari Cairan Limbah Tahu dan Sawit dengan menggunakan starter feses sapi - Yano, Yano Hurung Anoi (STTI Bontang, 2021)
Abstract Biogas is a type of gas produced through the anaerobic fermentation process of organic matter. One method of processing organic waste as an alternative energy source is biogas technology. This study aims to determine the effect of a mixture of cow feces with organic waste liquid on biogas productivity. The method used in this study is a small-scale experimental method. The results showed that the value of biogas efficiency from a mixture of cow feces and tofu waste was higher with a value of 2.8% compared to a mixture of cow feces and palm oil waste which was 1.77% and the calorific value of biogas mixed with cow feces and tofu waste had a higher calorific value 34918 ,8 cal/ltr compared to a mixture of cow feces and palm oil waste with a calorific value of 12986.47 cal/ltr. Keywords: Biogas, cow feces, tofu liquid waste, palm oil waste, efficiency and calorific value.